Peluang Usaha Mikro Kecil dan Menengah (UMKM) Dalam Pemasaran Ekonomi digital Di Sumatera Utara - Zahra, Aulia; Nisa Munthe, Ira Hairun; Miranda, Miranda; Rozi, Yudi Fakhrul; Nurbaiti, Nurbaiti (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to discuss the growth of UMKM and digital marketing opportunities and business challenges. Qualitative research is used in this research. Qualitative research is research that is descriptive in nature and tends to do analysis. The research findings show that digital technology growth, digital marketing opportunities, and micro, small, and medium enterprises (UMKM) are growing at an alarming rate. Apart from being a challenge for the business world, this also provides enormous opportunities and potential for economic growth and the business world, and actors in the business sector must be able to adapt to changing trends. information Technology. Utilizing digital developments in society and information technology, business actors must be able to create opportunities. Several policies from both the government and UMKM actors can encourage UMKM. The development of technology makes people tend to want the fastest service. This encourages UMKM to think more creatively in order to be able to meet the needs of society.